SHAHAR HOSIL QILUVCHI INDUSTRIYA – XORAZM VILOYATIDA URBANIZATSIYANING AYRIM MASALALARI - Ro‘zmetov, D.R. (SCIENCE and SOCIETY, 2025)
The article describes the types of city-forming forces and aspects of urban development at the current stage of urbanization of the Khorezm region. In particular, it describes the impact of urban construction, erected unevenly in rural areas, on the social development of the population.